O jogo autor-leitor na literatura do agora - Everton Vinicius de Santa (Estudos de Literatura Brasileira Contemporânea)
The issues involving authorship, the reader, the literary work and their relationships have been the focus of many theoretical approaches over traditional literary criticism, which already has clearly defined the roles of these three instances. However, in addressing the current practices of literature, especially considering the apparent immersion of authors and readers in cyberspace, I realize that these authors need a contemporary media exposure and use this to justify their choices in the creation of literary works or even to getting closer to their reader, person that would make their work gain significance. In this sense, Um erro emocional, by Cristovão Tezza, allow us to investigate this new author-reader game from, in the light of media exposure as evidenced by the virtual environments, and the theoretical issues that put these instances at different levels. Though focused on contemporary literature, I realize that although this approach between author and reader is not unprecedented, the influence of cyberspace in this process is evident.